Effects of Peace Marketing and Social Marketing Practice on Conflict Management: Mediating Role of Strategic Leadership (The Case from Mining Companies in East Guji Zone Oromia, Ethiopia) - Negeri, Dereje Dinsa (iRASD Journal of Management, 2023)
The main objective of this study is to assess the effects of peace marketing and social marketing practices on conflict management in the case of mining industries in Ethiopia's Oromia regional state of the East Guji zone. Farther more, the study helps the mining industry owners understand the effects of peace marketing and social marketing practices on conflict management which leads to peace and harmony between the company and the surrounding community that sustains long lasting peace and profitability of the company. The study has relevant literature and a considerable discussion of the effects of peace and social marketing on conflict management with the mediating role of strategic leadership. According to various researchers, peace marketing is a somewhat fresh idea in place of a non-return market in collaboration with social marketing practices to create peace. (Al-taie et al., 2022). As a result, this research aimed to investigate the effects of the peace market and social marketing practice in conflict resolution from mining companies in Ethiopia, East Guji zone of Oromia regional state. The study employed a Quantitative research design method using a survey questionnaire to collect data. The data analysis was done using the structural equation modeling technique (SEM), and 400 respondents were taken as a sample size. The analyzed result shows that peace marketing and social marketing practice has an appositive and significant effect on conflict management as well as strategic leadership is the best mediator among peace marketing and social marketing practice on conflict management.